Additive manufacturing of polyaniline-based materials: an opportunity for new designs and applications in energy and biotechnology. (March 2022) - Menzel, Valentin C; Tudela, Ignacio
Graphical abstract: AM techniques for the fabrication of 3D structures using PANI or PANI-composites: Direct Ink Writing (DIW) and its subtypes Ink-Jetting and Continuous Filament Writing (CFW); Fused Deposition Modelling (FDM) and Direct Light Printing (DLP). Abstract : Intrinsically conductive polyaniline possesses many desirable physical, chemical and biological properties. Combining those with the enhanced design flexibility, structural complexity and environmental sustainability of additive manufacturing opens up a whole new field for the design and development of various applications, from energy storage over printable electronics to conductive implants. However, additive manufacturing of polyaniline is still in the early stages and remains full of challenges and limitations to overcome. This paper gives a critical overview of this emerging field and the different 3D printing techniques for polyaniline and polyaniline-based composites, along with an outlook of areas with high potential for future research.